Treatment of a Severe Pediatric Lyell Syndrome with Amniotic Membrane: Case Report and Histological Findings - Azzena B.; Tiengo C.; Giatsidis G.; Salmaso R.; Pontini A. (Journal of Tissue Repair and Regeneration, 2018)
Background: Lyell Syndrome (TEN, Toxic epidermal necrolysis) represents a medical emergency particularly in pediatric patients in whom the massive skin damage can quickly lead to multi-organ dysfunction and death. Prompt restoration of the physiologic mucosal/cutaneous barrier is mandatory. The use of amniotic membranes has been described in the treatment of ophthalmic Lyell Syndrome, but its use has not yet been adopted for the management of larger cutaneous wounds. Study Hypothesis: Here we report the use of amniotic membranes in a pediatric case of severe Lyell Syndrome with complete skin surface, ocular and mucosal involvement with life threating presentation. Methods: A 7-year old female was admitted to our Burn Centre for severe cutaneous/mucosal exfoliation (100% Total body surface area, TBSA) as a result of an adverse reaction to ibuprofen administration. Supportive fluid administration, cardiac-pulmonary assistance and pain management were complemented by serial grafting of amniotic membranes on all affected areas to provide coverage of the exfoliated skin/mucosa. Biopsies were obtained to monitor histological skin changes. Results: The patient showed an excellent response to amniotic membrane treatment, with rapid restoration of mucosal and cutaneous layers in the grafted areas. This resulted in a decreased need for dressing changes, avoidance of additional surgeries and a reduced dependence on supportive therapy. Lower pain levels than usually expected led to a reduced need for narcotic pain medications and allowed for early physical rehabilitation and a short hospital stay. Histology confirmed evidence of topical immune-modulation in treated areas (reduction of inflammatory infiltrate). Conclusion: As we tested in numerously TEN and burn pediatric injuries Amniotic membranes with their regenerative and immune-modulatory effects may represent an life saving treatment even in the worst cases of pediatric Lyell syndrome.
Keywords: Toxic epidermal necrolysis